Non-Specific Steroid Cell Tumor of The Ovary: Case Report And Review of The Literature - M. Darouichi (Journal of Digestive Disorders And Diagnosis, 2022)
Steroid cell tumors of the ovary are particularly rare, secreting sex hormones, characterized by steroid cell proliferation and represent only 0.1% of all ovarian tumors. They are classified into three subtypes according to their cell of origin: stromal luteoma, Leydig cell tumors and a third subtype of unknown lineage corresponds to a not specified steroid cell tumor (SCT-NOS). This third subtype accounts for 60% of steroid cell tumors. The clinical manifestations of SCT-NOS can take many forms, including pain, abdominal distension, but perhaps the most visible presentations are those related to hormonal activity and virilization of the tumor. We present a rare case of a 48-year-old woman with vaginal bleeding and a history of trunk obesity, hirsutism for 2 years and hypothyroidism with hormone replacement therapy. Clinical examination revealed a characteristic of obesity, virilization. Serum testosterone was 3.62 µg / L and CA-125 was 40.67. Magnetic resonance imaging identified a left ovarian solid mass and histopathology confirmed a steroid cell tumor not specific. The patient underwent exploratory laparotomy and left salpingoophorectomy. Macroscopically, the mass is well circumscribed, solid, homogeneous and yellowish. Microscopically, the tumor is mainly composed of eosinophilic or vacuolar granular cytoplasm. Immunohistochemistry showed that the tumor cells were strongly positive for inhibin. The postoperative period was uneventful. Through this rare observation, we will discuss the aspects that characterize this type of tumor and present some guidelines to be used in the differential diagnosis, as well as the difficulties encountered in the clinical, radiological and therapeutic fields.
Keywords: Steroid Cell Tumor